Random Mutagenesis of the Aspergillus oryzae Genome Results in Fungal Antibacterial Activity - Cory A. Leonard; Stacy D. Brown; J. Russell Hayman (International Journal of Microbiology)
Multidrug-resistant bacteria cause severe infections in hospitals and communities. Development of new drugs to combat resistant microorganisms is needed. Natural products of microbial origin are the source of most currently available antibiotics. We hypothesized that random mutagenesis of Aspergillus oryzae would result in secretion of antibacterial compounds. To address this hypothesis, we developed a screen to identify individual A. oryzae mutants that inhibit the growth of Methicillin-resistant Staphylococcus aureus (MRSA) in vitro. To randomly generate A. oryzae mutant strains, spores were treated with ethyl methanesulfonate (EMS). Over 3000 EMS-treated A. oryzae cultures were tested in the screen, and one isolate, CAL220, exhibited altered morphology and antibacterial activity. Culture supernatant from this isolate showed antibacterial activity against Methicillin-sensitive Staphylococcus aureus, MRSA, and Pseudomonas aeruginosa, but not Klebsiella pneumonia or Proteus vulgaris. The results of this study support our hypothesis and suggest that the screen used is sufficient and appropriate to detect secreted antibacterial fungal compounds resulting from mutagenesis of A. oryzae. Because the genome of A. oryzae has been sequenced and systems are available for genetic transformation of this organism, targeted as well as random mutations may be introduced to facilitate the discovery of novel antibacterial compounds using this system.